2004
DOI: 10.1074/jbc.m304950200
|View full text |Cite
|
Sign up to set email alerts
|

The C- and the N-terminal Regions of Glycoprotein 41 Ectodomain Fuse Membranes Enriched and Not Enriched with Cholesterol, Respectively

Abstract: To infect target cells, HIV-1 employs a virally encoded transmembrane protein (gp41) to fuse its viral envelope with the target cell plasma membrane. We describe the gp41 ectodomain as comprised of N-and C-terminal subdomains, each containing a heptad repeat as well as a fusogenic region, whose organization is mirrored by the intervening loop region. Recent evidence indicates that the gp41 directed fusion reaction proceeds to initial pore formation prior to gp41 folding into its low energy hairpin conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
207
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(223 citation statements)
references
References 54 publications
16
207
0
Order By: Relevance
“…This region is proximal to a predicted TM domain (Figure 2A), which was identified using the WW octanol hydrophobicity scale that allows for the identification of TM helices of membrane proteins with very high accuracy (73). On the basis of these observations, it is unlikely that the aromatic domain is part of the TM anchor as previously predicted by Rota et al (6), rather, as described for the aromatic domains of HIV-1 and EboV (10,55,56,58), this region is most likely an independent domain proximal to the TM anchor of the S2 subunit.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This region is proximal to a predicted TM domain (Figure 2A), which was identified using the WW octanol hydrophobicity scale that allows for the identification of TM helices of membrane proteins with very high accuracy (73). On the basis of these observations, it is unlikely that the aromatic domain is part of the TM anchor as previously predicted by Rota et al (6), rather, as described for the aromatic domains of HIV-1 and EboV (10,55,56,58), this region is most likely an independent domain proximal to the TM anchor of the S2 subunit.…”
Section: Resultsmentioning
confidence: 68%
“…The resulting structure is believed to align the fusion peptide, aromatic domain, and TM anchor (30), resulting in viral/ cell membrane fusion. On the basis of the observations that (1) the aromatic peptides of coronaviruses and other viruses (10,55,56,58) strongly interact with and disrupt membranes and (2) the overall conservation of these sequences in many viruses, we hypothesize that the aromatic domain of class I viral fusion proteins plays a critical role in viral/cell membrane fusion. Specifically, we propose that the aromatic domain, in conjunction with the fusion peptide and the TM anchor, forms a continuous track of hydrophobic, membraneinteracting surfaces that provide a low-energy (low-barrier) path for lipid flow and membrane fusion during virion/cell fusion ( Figure 7).…”
Section: Coronavirus Aromatic Domainmentioning
confidence: 99%
“…Peptides composed of the HFP sequence induce fusion between large unilamellar vesicles (LUVs) and between erythrocytes (5,6). There are similar mutation/fusion activity relationships for HFP-induced fusion and HIV-induced fusion which suggests that HFP is a useful model system to understand some aspects of viral/target cell fusion (7-10).There is also evidence for participation of other regions of gp41 in membrane fusion (11)(12)(13)(14).There are atomic-resolution structures of the "soluble ectodomain" of gp41 which does not contain the ∼30 N-terminal residues of gp41 (including the HFP) (2,(15)(16)(17)(18)(19). These structures are believed to correspond to the conformation after fusion has occurred and perhaps during some fusion steps (20).…”
mentioning
confidence: 66%
“…8a). The two-spin (three-spin) model has two (three) adjacent in-register parallel β strands and the simulations are based on two (three) 13 COs, each of which is at the same residue position in its respective strand. The interstrand distance and corresponding d CC value were input parameters for the simulations.…”
mentioning
confidence: 99%
“…This pattern plays an important role in both the early and late stages of the membrane fusion (Chan and Kim, 1998;Johnson et al, 2001;Liu et al, 2005;Lu et al, 1995;Munoz-Barroso et al, 1998). This process can also participate in the formation of the fusion pore through direct proteinmembrane interactions (Munoz-Barroso et al, 1998;Shnaper et al, 2004). Different studies have shown the immunogenicity of the fusogenic complex and describe Abs direct against this structure (Gustchina et al, 2010;Opalka et al, 2004;Vincent et al, 2008).…”
Section: Fusogenic 6 Helix-bundle Formmentioning
confidence: 99%